Environmental performance in manufacturing companies: a benchmarking study. Issue 2 (3rd November 2020) - Trujillo-Gallego, Mariana; Sarache, William; Sellitto, Miguel Afonso
Abstract : Purpose: This study aims to explore manufacturing companies' environmental performance with the green supply chain management (GSCM) approach, taking into account company size, geographic region, industrial sector, target market and environmental management maturity level. Design/methodology/approach: Based on the literature review, five propositions were put forward. An empirical study, using survey research, was completed. The survey questionnaire was designed with 46 items, using both the literature and industry expert input. Statistical analysis was employed to test the propositions in a sample of 116 Colombian manufacturing companies. Findings: The test results indicate that significant environmental performance differences exist, given company sizes and target markets. However, no statistical significance was found involving the geographic region or industrial sector. Significant differences were found in maturity levels between the three clusters identified: reactive, preventive and proactive. Although the companies in the proactive group performed better, they still lagged in green practices that implied integration with suppliers and customers. Practical implications: This study provides empirical evidence regarding the profile of those manufacturing companies that achieve better environmental performance. Moreover, the results yield insights for the generation of continuous improvement processes in companies with lower performance. Originality/value: Few empirical studies have been carried out in GSCM that integrate specific factors in the environmental performance assessment of manufacturing companies in developing countries. On the other hand, the results permit the identification of the profile of those companies with greater maturity in their environmental practices.